Bispectral Index During Maintenance of Total Intravenous Anesthesia: Frequency of Out of Recommended Range and Impact of Patients' Characteristics. (August 2020) - Gross, Tommy; Feliot, Elodie; Gayat, Etienne; Chazot, Thierry; Liu, Ngai; Fischler, Marc; Bobet, Mathieu; Le Guen, Morgan
Abstract : Little is known about respecting the recommended range of bispectral index (BIS) in practice. This exploratory retrospective analysis of 138 robotic surgical patients having received total intravenous anesthesia shows that BIS was between 40 and 60 during 61.3% ± 25.2% (mean ± standard deviation [SD]) of maintenance, >60 during 3.1% ± 5.5%, and <40 during 35.7% ± 26.9%. Burst suppression was present during 17.8% ± 22.2%. Female sex is associated with increased periods of BIS <40 ( P = .002) as is body mass index (BMI) <26 ( P = .012). Increased age is associated with increase in burst suppression ( P = .005). A larger study is required to confirm the role of patients' factors on the number of periods of low BIS.